Graves' disease: Epidemiology, genetic and environmental risk factors and viruses. Issue 1 (January 2020) - Antonelli, Alessandro; Ferrari, Silvia Martina; Ragusa, Francesca; Elia, Giusy; Paparo, Sabrina Rosaria; Ruffilli, Ilaria; Patrizio, Armando; Giusti, Claudia; Gonnella, Debora; Cristaudo, Alfonso; Foddis, Rudy; Shoenfeld, Yehuda; et al.
Abstract : Graves' disease (GD) is the most common cause of hyperthyroidism in developed Countries. It is more common between 30 and 60 years; 5–10 times more frequent in women. The genetic predisposition accounts for 79% of the risk for GD, while environmental factors for 21%. About 70% of genes associated with autoimmune thyroid disorders (AITD) are implicated in T-cell function. Among GD endogenous factors, estrogens, X-inactivation and microchimerism are important. Among environmental risk factors, smoking, iodine excess, selenium and vitamin D deficiency, and the occupational exposure to Agent Orange have been associated with GD. Many studies showed that HCV is associated with thyroid autoimmunity and hypothyroidism, in patients with chronic HCV hepatitis (CHC); a significant link has been shown also between HCV-related mixed cryoglobulinemia and risk for GD. Moreover, IFN-α-treated CHC patients develop GD more frequently. Novel studies are needed about possible risk factors to reduce the occurence of GD in West Countries.